MAKNA TRADISI YASINAN PADA ACARA MAULID Al-MAHMUD: Kajian Living di Pondok Pesantren Salafiyah, Grogol, Blotongan Salatiga) - Nahya Nur Aini; Didah Nurfaridah; Aulia Shofiana (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This article examines the meaning of the Yasinan tradition at the Al-Mahmud maulid event in providing spiritual peace of mind carried out at the Salafiyah Grogol Blotongan Islamic Boarding School in Salatiga City. This article includes a living Quran study, so the research method uses qualitative methods with several data collection techniques including: observation and interviews, with a phenomenological approach to Alfred Schutz's theory, namely the because of motive and in order to motive. Because of motive Salafiyah Islamic Boarding School does the tradition is in addition to the motive of praying for the spirits of ancestors also aims as self-protection from an empty soul to avoid the supernatural and become a repellent, such as trance through the maulid Al-Mahmud event. The in order to motive of the tradition is the manifestation of mutual cooperation, social solidarity, sympathy and empathy is also another side of the Yasinan tradition at the Maulid Al-Mahmud event. In fact, the recitation of Maulid Al-Mahmud is also a form of praise, respect and love for the Holy Prophet Muhammad. This is a collaboration between wirid in the form of sholawat and the Quran, not just a warning or guidance, but also as a person's foundation from an empty heart (Peace of mind).